2011
DOI: 10.3727/109830511x13167968595741
|View full text |Cite
|
Sign up to set email alerts
|

Myswitzerland.com: Analysis of Online Communication and Promotion

Abstract: This research investigates the current state of technology adoption of a popular tourism destination: Switzerland. This case study has been elaborated leveraging on existing literature, public documents, and private statistics; it describes the importance of technology-mediated communication and promotion within the Swiss National Tourism Board, highlighting the achievements and envisaging the future steps. Thanks to an online communication model, the website of the Swiss Tourism Board (MySwitzerland.com) has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…On the one side, tourism companies and organizations are understanding that a proper strategic and tactical use of technologies can bring a competitive added value (Inversini, Brülhart, & Cantoni, 2012). Consumers become much more sophisticated and, thanks to the Internet, they have the possibility of looking for different options while choosing their travel plans (Buhalis & Law, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the one side, tourism companies and organizations are understanding that a proper strategic and tactical use of technologies can bring a competitive added value (Inversini, Brülhart, & Cantoni, 2012). Consumers become much more sophisticated and, thanks to the Internet, they have the possibility of looking for different options while choosing their travel plans (Buhalis & Law, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Kronenberg et al (2015) conducted a research focused on the effect of advertising on international tourism demand at the destination level and showed that advertising is a significant factor of tourism demand while income and tourism price levels were found less significant. Internet based technology together with a realistic use of the online communication channel are already proven marketing tools and even often described as key success factor of DMO communication (Inversini et al, 2011). Furthermore, online promotion can improve the destination loyalty (Lai & Vinh, 2013) but can equally have both positive and negative implications on potential tourists (Yazdanifard & Yee, 2014;Saß, 2011).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Nowadays, ICTs have a key role in determining the competitiveness of the tourism industry by providing tools to support effectively the development, management and distribution of offers on the global market, as well as interaction with consumers (Buhalis, 2003). Direct dialogue with customers, actual ones and prospects, is enabled in a cost--effective way by the internet, which assists tourism suppliers in the use of a wide range of online promotional activities to integrate, if not substitute, offline promotions (Inversini et al, 2012). As a matter of fact, as first acknowledged by Buhalis (1998), the internet is one of the most relevant technologies affecting the tourism sector.…”
Section: Tourism and Ictmentioning
confidence: 99%